(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Over the past few decades and even now, public health assessment is primarily conducted based on data characterizing indicators such as the total population size, physical development, morbidity, disability, and mortality. Of course, such an approach to assessing health does not seem quite reliable, because although the state of physical development can indeed to some extent characterize the level of human health, cases of illness do not determine the level of health, but provide information about its disruption, the development of one or another pathological process in the body. Unfortunately, to date, criteria and indicators that fully determine the health status of people have not been developed or defined, and direct integral indicators and criteria that can be used for these purposes are difficult to assess the level of human health, especially in organized communities and at the population level as a whole.